Remitted euros are not equal: The complex spending behaviour of Kosovar households - Arjola Arapi-Gjini; Judith Möllers; Thomas Herzfeld (International Migration, 2024)
This article uses a mixed-methods approach to evaluate how remittances impact household spending behaviour in Kosovo. Based on a nationally representative data set and using matching techniques, it shows that migration does not cause substantive changes in household spending. While remittances cover basic consumption needs, there are no impacts on budgetary allocations for business investments, health and education. Yet, qualitative research conducted in Kosovo's Opoja region, involving the analysis of 28 open-ended interviews, unveils a complex remitting mechanism. While migrants send smaller but regular amounts of money to cover basic needs, earmarked transfers are allocated for housing investments and conspicuous consumption only. These earmarked transfers do not enter Kosovar households' budgets, as migrants exercise decision-making authority over these funds. For policymakers, our findings suggest that standard survey questions fall short of capturing the complexity of the remitting mechanism. When promoting productive investments, it is the migrants who should be targeted as key decision-makers.
Keywords: 330